Unraveling the role of prenyl side-chain interactions in stabilizing the secondary carbocation in the biosynthesis of variexenol B - Nakano, Moe; Gemma, Rintaro; Sato, Hajime (Beilstein Journal of Organic Chemistry, 2023)
Terpene cyclization reactions involve a number of carbocation intermediates. In some cases, these carbocations are stabilized by through-space interactions with π orbitals. Several terpene/terpenoids, such as sativene, santalene, bergamotene, ophiobolin and mangicol, possess prenyl side chains that do not participate in the cyclization reaction. The role of these prenyl side chains has been partially investigated, but remains elusive in the cyclization cascade. In this study, we focus on variexenol B that is synthesized from iso-GGPP, as recently reported by Dickschat and co-workers, and investigate the possibility of through-space interactions with prenyl side chains using DFT calculations. Our calculations show that (i) the unstable secondary carbocation is stabilized by the cation–π interaction from prenyl side chains, thereby lowering the activation energy, (ii) the four-membered ring formation is completed through bridging from the exomethylene group, and (iii) the annulation from the exomethylene group proceeds in a barrier-free manner.
Keywords: biosynthesis; carbocation; cation–π interaction; DFT; terpene